The Impact of Respiratory Syncytial Virus Undertesting on Estimates of Disease Burden and Vaccine Effectiveness in a Large Integrated Healthcare System - Bradley K Ackerson; Brandon Chia; Negar Aliabadi; Gabriella Goodwin; Jeff Slezak; Vennis Hong; Qing Liu; Sally Shaw; Sabrina Welsh; Julie A Stern; Banshri Kapadia; Brigitte C Spence; et al. (Open Forum Infectious Diseases, 2026)
Abstract Infrequent standard-of-care (SOC) testing for respiratory syncytial virus (RSV) in adults with acute respiratory illness (ARI) contributes to underestimated disease burden. We compared RSV prevalence and RSV vaccine effectiveness (VE) among 14,044 adults ≥60 years with ARI ED/hospital admissions receiving SOC RSV testing versus those with SOC or salvaged respiratory specimen RSV testing. RSV was identified in 139 (0.99%) specimens by SOC testing alone versus 483 (3.44%) via SOC combined with salvage testing. Precision of VE against RSV-related ARI ED/hospital admissions improved substantially with inclusion of salvage testing compared to SOC testing alone (92% [67%- 98%] vs 90% [29%- 99%]).